Pusa hispida ... - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Pusa hispida (Schreber, 1775) —Ringed Seal Phoca hispida Schreber, 1775 p.l86 (1776 p312); Type locality- Coast of Greenland and Labrador. Phoca hispida ochotensis: Won, 1967 p.92. Pusa hispida: Won, 1968 p.339; Kim, 2004 p.195. Pusa hispida ochotensis: Kim, 2004 p.196. Range: Ringed seals rarely occur in the Yellow Sea along the Korean coast and is thus considered a vagrant species (Fig. 65). Remarks: Although recent comprehensive morphological examinations did not support division of the Arctic population into multiple subspecies (Amano et al. 2002), Berta and Churchill (2012) recommended continued recognition of Okhotsk ringed seals around Okhotsk Sea, P. h. ochotensis (Pallas, 1811). The Society for Marine Mammalogy has used ‘(Nordquist, 1889)’ as the original author and year citation for the ringed seal; however, the correct author and name for the subspecies, O. h. ochotensis is ‘(Pallas, 1811)’. Conservation status: The Ministry of Environment designated P. hispida an Endangered Species in 1997 but ... : Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on page 101, DOI: 10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198 ...